Pemanfaatan Tanaman Obat Keluarga (TOGA): Curcuma Domestica Val. Dan Caesalpinia Sappan L. Di Desa Dadapan Lamongan - Fita Fitriatul Wahidah; Lilik Erviani; Merinda Nur Indahsari; Rahmah Arfiyah Ula; Sitti Nur Ilmiah; Trisnani Alif (Jurnal Masyarakat Mengabdi Nusantara, 2023)
The majority of people in Dadapan village earn their livelihood as farmers, so we can find many plants which have medicinal properties in their yards. However, the knowledge of the Dadapan Village community regarding the use of medicinal plants tends to be lacking. So, a new breakthrough alternative is needed to introduce TOGA to the people in Dadapan Village. Turmeric and secang wood are two of the many TOGA plants that can be used as family medicine. Most of PKK and ASMAN TOGA members are housewives so making ready-to-drink herbal medicine from TOGA plants grown by themselves can be a beneficial activity for the family, and improve the family economy. The results of the questionnaire that has been carried out show that this training is able to increase knowledge about the benefits and methods of making turmeric and secang herbal medicine ready to drink. The percentage before the training was carried out was 73.19%, while after the training it was 97.24, meaning there was an increase in participants' understanding about TOGA by 24.05%.